Lymph node metastasis of carcinomas of transverse colon including flexures. Consideration of the extramesocolic lymph node stations - Perrakis, Aristotelis; Weber, Klaus; Merkel, Susanne; Matzel, Klaus; Agaimy, Abbas; Gebbert, Carol; Hohenberger, Werner (International Journal of Colorectal Disease, 2014)
Complete mesocolic excision (CME) is nowadays state of the art in the treatment of colon cancer. In cases of carcinoma of transverse colon and of both flexures an extramesocolic lymph node metastasis can be found in the infrapancreatic lymph node region (ILR) and across the gastroepiploic arcade (GLR). These direct metastatic routes were not previously systematically considered. In order to validate our hypothesis of these direct metastatic pathways and to obtain evidence of our approach of including dissection of these areas as part of CME, we initiated a prospective study evaluating these lymph node regions during surgery.Forty-five consecutive patients with primary tumour manifestation in transverse colon and both flexures between May 2010 and January 2013 were prospectively analyzed. Patients were followed up for at least 6 months. Mode of surgery, histopathology, morbidity and mortality were evaluated.Twenty-six patients had a carcinoma of transverse colon, 16 patients one of hepatic flexure and four patients one of splenic flexure. The median lymph node yield was 40. Occurrence of lymph node metastasis in ILR was registered in five patients and in GLR in four patients. The mean lymph node ratio was 0.085. Postoperative complications occurred in nine patients, and postoperative mortality was 2 %.We were able to demonstrate this novel metastatic route of carcinomas of the transverse colon and of both flexures in ILR and GLR. These could be considered as regional lymph node regions and have to be included into surgery for cancer of the transverse colon including both flexures.
EVALuna2:6599